Andexanet versus prothrombin complex concentrates: Differences in reversal of factor Xa inhibitors in in vitro thrombin generation. Issue 8 (27th August 2020) - Lu, Genmin; Lin, Joyce; Bui, Khanh; Curnutte, John T.; Conley, Pamela B.
Abstract: Background: Andexanet alfa (andexanet) is a modified human factor Xa (FXa) approved for anticoagulation reversal in patients with life‐threatening bleeding treated with rivaroxaban or apixaban. Four‐factor prothrombin complex concentrates (4F‐PCCs) are approved for reversal of vitamin K antagonist–induced anticoagulation but not FXa inhibitors. The mechanism and effectiveness of 4F‐PCCs for FXa inhibitor reversal are unclear. Objective: To investigate the mechanism and impact of 4F‐PCCs on reversal of rivaroxaban and apixaban in vitro compared to andexanet. Methods: The effect of 4F‐PCCs (or individual factors) on tissue factor‐initiated thrombin generation (TF‐TG) was evaluated in human plasma, with or without rivaroxaban or apixaban, and compared with andexanet under the same conditions. Results: In the TF‐TG assay, 4F‐PCC completely reversed warfarin anticoagulation. Andexanet normalized TF‐TG over a wide range of apixaban and rivaroxaban concentrations tested (19‐2000 ng/mL). However, 4F‐PCC (or individual factors) was unable to normalize endogenous thrombin potential (ETP) or peak thrombin (Peak) in the presence of apixaban or rivaroxaban (75‐500 ng/mL). TF‐TG was only normalized by 4F‐PCC at inhibitor concentrations <75 ng/mL (ETP) or <37.5 ng/mL (Peak). These data can be explained by the estimated thresholds of FXa activity required to support normal TF‐TG based on the inhibitor:FXa ratios and levels of uninhibited FXa. The data are consistent with healthy volunteer studies where TF‐TG is not normalized until inhibitor levels are substantially decreased. Conclusions: Both the theoretical calculations and experimental data demonstrated that 4F‐PCCs are only able to normalize TG over a low and narrow range of FXa inhibitor concentrations (<75 ng/mL).